2019
DOI: 10.1039/c9cy00618d
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative dehydrogenation of ethylbenzene to styrene over the CoFe2O4–MCM-41 catalyst: preferential adsorption on the O2−Fe3+O2− sites located at octahedral positions

Abstract: The present study describes the catalytic performance of cobalt ferrite supported on MCM-41 for the oxidative dehydrogenation of ethylbenzene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…The previous studies have reported the ethylbenzene dehydrogenation mechanism. , In this case, we proposed a CL-ODH reaction pathway for ethylbenzene conversion (Scheme ). First, ethylbenzene was adsorbed to the Mn 4+ active site by hemolytic cleavage.…”
Section: Resultsmentioning
confidence: 93%
“…The previous studies have reported the ethylbenzene dehydrogenation mechanism. , In this case, we proposed a CL-ODH reaction pathway for ethylbenzene conversion (Scheme ). First, ethylbenzene was adsorbed to the Mn 4+ active site by hemolytic cleavage.…”
Section: Resultsmentioning
confidence: 93%
“…It is worth mentioning that surface electrostatic potential maps have been extensively studied to assess the acidity of metallic oxides by visualizing the surface charge distribution, which is related to the change of colors concerning more positive (blue) or negative regions (red). 68,69 Thus, Fig. 12b presents the electron density for the Al 2 O 3 phase (001).…”
Section: Resultsmentioning
confidence: 99%
“…Utilizing Néel law, K eff = 25 k B T B / V m , the magnetic anisotropy constant ( K eff ) was calculated for all nanoferrites, where k B is Boltzmann’s constant (1.3807 × 10 –23 J/K) and V m is the volume of a single nanocrystal assuming sphere as V m = π D m 3 /6 ( D m is the magnetic core diameter from TEM). , For all nanoferrites, there is a peak in the ZFC measurements, indicating a blocking behavior, with the blocking temperature T B well below room temperature (300 K). FC/ZFC curves converged at temperatures higher than the blocking temperatures ( T > T B ).…”
Section: Resultsmentioning
confidence: 99%